Design of Acoustic Signals for a Seal Deterrent Device - Aboltins, Arturs; Grizans, Juris; Pikulins, Dmitrijs; Terauds, Maris; Zeltins, Maris (Electrical, Control and Communication Engineering, 2020)
During the past decade, attacks by grey seals on fishing nets in the Baltic Sea have caused considerable loss of fish catch and damage to fishing gears. One of the approaches to reduce the number of seal attacks on fishing nets is to use acoustic deterrent devices (ADDs). Unfortunately, most of the commercially available ADDs are not well suited to the deployment in the sea and require considerable additional investments. The objective of the present research is to develop a compact and cost-efficient ADD for deployment in the sea environment. This paper is devoted to the design of acoustic signals for a prototype ADD. Signals from other experimental and commercially available ADDs are studied and compared. Moreover, limitations imposed by the underwater environment, transducers, battery power, and fish hearing are analysed and considered during the development of signal patterns. The results of tests conducted in an artificial reservoir and in the sea are presented.